Has your house got cracks? a homeowner's guide to subsidence and heave damage - Freeman, T. J. (Thomas Telford, 2002)
The first edition dealt specifically with the problems associated with properties founded on shrinkable clay soils, and was reprinted many times. The second edition has been expanded to include sections on other types of subsidence and causes of damage that are unrelated to foundation movement.